Dilemmas pertaining to the heritage processes in the Pâ€™urhépecha region. A journey between the 19th and 21st centuries (Tzintzun, Revista de Estudios Históricos, 2020)
The central elements addressed in this article are the processes, tensions and dilemmas that arose from the study of public policies of recognition of the Pâ€™urhépecha cultural heritage. This article will present a synthesis of this problem that we jointly focus on as dilemmas derived from a process that has become more acute and has shown new developments, especially in the last two decades, now in the form of public policies that tend to centralize decisions regarding the management of culture. Our goal is to reflect on these long-term processes, which we see as being in a consolidation stage at the beginning of the 21st century, under the Magical Towns program created in 2001, from which the so-called Don Vasco Route derived in 2011, while some manifestations originated in the indigenous communities against exclusion and the way in which these policies have been implemented.